The ice beneath her : a novel - Grebe, Camilla (Ballantine Books, 2016)
As winter's chill descends on Stockholm, homicide detectives Peter Lindgren and Manfred Olsson arrive at a crime scene, a posh suburban home where an unidentified woman was beheaded--a murder made more disturbing by its uncanny resemblance to an unsolved killing ten years earlier. As the detectives search for motives and the homeowner, CEO Jesper Orre, they enlist the help of retired criminal profiler Hanne Lagerlind-Schön. But they aren't the only ones searching. A young clerk from Orre's company, Emma Bohman, had an affair with Orre right before he disappeared. One staggering misfortune after another followed, leaving Emma certain that Orre was to blame. Pursuing the same man for different reasons, Emma and the police are destined to cross paths in a chilling dance of obsession, vengeance, madness, and love gone hellishly wrong. --